REGULARITIES OF COMMUNICATION SKILLS FORMATION IN BORDER GUARD TRAINING PROCESS - Indriksons, Alens (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The present paper explores specificity of communication process and formation of communication skills in militarized educational institutions working on the basis of vertical (downward) communication.  Service and “subject – object” relationships build up a barrier between teaching staff and students, since there is a difference in service ranks and holding positions interfering with a successful communication process turning it into unfinished process, without which a successful formation of communication skills is impossible. The paper covers the problems in formation of communication skills in Border Guard training process and the author try to find out correlations and regularities of communication skills formation in militarized educational institution.